2007
DOI: 10.2175/106143006x111763
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Treatment of High‐Saline Wastewater Using Halophilic Methanogens in Laboratory‐Scale Anaerobic Filters

Abstract: The presence of a high concentration of sodium in wastewater is considered inhibitory for anaerobic biological treatment. This research was designed to investigate the potential use of halophilic methanogens and a mixed culture of halophilic methanogens and digester sludge, in anaerobic filters, for treatment of organic pollutants in high-saline wastewater at 358C. Data related to startup of the filters are presented. Both halophilic and mixed-culture anaerobic filters were able to operate at a sodium chloride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…However, sodium is known to inhibit anaerobic treatment of organics, and given the advantages of anaerobic digestion such as methane evolution and low sludge production, it would be desirable if these wastewaters could be treated anaerobically. Nevertheless, several studies using anaerobic biomass reported adequate organic removal by employing strategies such as a long biomass adaptation period to salinity , , bioaugmentation with halophilic microorganisms , , marine inocula , membrane bioreactors , and anaerobic digestion followed by aerobic treatment . However, most of these studies only investigated a gradual increase in salinity despite the fact that it is often highly variable in many industrial wastewaters .…”
Section: Introductionmentioning
confidence: 99%
“…However, sodium is known to inhibit anaerobic treatment of organics, and given the advantages of anaerobic digestion such as methane evolution and low sludge production, it would be desirable if these wastewaters could be treated anaerobically. Nevertheless, several studies using anaerobic biomass reported adequate organic removal by employing strategies such as a long biomass adaptation period to salinity , , bioaugmentation with halophilic microorganisms , , marine inocula , membrane bioreactors , and anaerobic digestion followed by aerobic treatment . However, most of these studies only investigated a gradual increase in salinity despite the fact that it is often highly variable in many industrial wastewaters .…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this issue the progressive adaptation of sludge to high salinity or the use of adapted inoculum are present as suitable strategies to achieve a stable methanogenic activity at conditions of high salt concentrations . A comparison between both strategies show that similar organic loading removal rates and COD removal efficiencies can be achieved treating wastewaters with 35 g NaCl/L (Riffat & Krongthamchat, 2007). Gradual acclimation of anaerobic biomass to Na + enables an increase in the tolerance of methanogens to this cation.…”
Section: Anaerobic Treatmentmentioning
confidence: 94%
“…To overcome this issue the progressive adaptation of sludge to high salinity or the use of adapted inoculum are present as suitable strategies to achieve a stable methanogenic activity at conditions of high salt concentrations (Aspé et al, 1997;Omil et al, 1995). A comparison between both strategies show that similar organic loading removal rates and COD removal efficiencies can be achieved treating wastewaters with 35 g NaCl/L (Riffat & Krongthamchat, 2007). Gradual acclimation of anaerobic biomass to Na + enables an increase in the tolerance of methanogens to this cation.…”
Section: Anaerobic Treatmentmentioning
confidence: 99%